The correlation between CK MB curve type and the clinical course of recent myocardial infarction - Korewicki, J; Opolski, G; Ostrzycki, A; Zieliński, T; Jankowski, K (Cor et vasa, 1988)
In 265 patients with acute myocardial infarction (MI) for whom the 72-hour CK MB curve was obtained, three types of a curve were found: with a single and early 16 h peak value (type A), with a single late 16 h peak value (type B), and with a double peak (type C). Type A of the CK MB curve was found in 32% of patients with acute MI, type B in 55% and type C in 13%. There were no significant differences of CK MB max between the type groups. Infarct size differed significantly between groups (A-29 +/- 19, B-35 +/- 22, C-53 +/- 30 g Eq CK MB). In-hospital mortality also differed significantly particularly between type C (31%) and type A groups (5%). Nitroglycerin or practolol given intravenously during the first 48 hours changed the CK MB curve mainly by decreasing CK MB max as compared to controls treated conventionally. There was no effect of treatment with either nitroglycerin or practolol on the clinical course in patients with type A CK MB curve. There is a good correlation between the CK MB curve type and the clinical course of MI. Nitroglycerin or practolol decreased the infarct size only in patients with either B or C type of CK MB curve, having no influence in patients with a mild form of acute MI (type A).
Keywords: Polsko; Myocardial Infarction; infarkt myokardu; lidé středního věku; Practolol; praktolol; kreatinkinasa; nitroglycerin; Humans; Shock, Cardiogenic; Middle Aged; senioři; prognóza; Prognosis; Aged; Creatine Kinase; kardiogenní šok; Nitroglycerin; Adult; Isoenzymes; Heart Failure; srdeční selhání; izoenzymy; Poland; dospělí; lidé